1990
DOI: 10.1002/maco.19900411209
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion behaviour of Ni3Al alloys in SO2‐containing combustion gases

Abstract: The high temperature corrosion behaviour of some nickel aluminides alloyed with zirconium or hafnium is presented. The corrosion tests were carried out in the temperature range 920 to 1010 "C, both in air and in atmospheres containing sulphur dioxide, using a thermobalance.The results obtained in air show that all the nickel aluminides display sufficient corrosion resistance up to 920 "C. Nickel aluminide alloyed with hafnium is more resistant than the aluminide alloyed with zirconium. The oxide layer on the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1994
1994
2007
2007

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…In the case of the high temperature sulphidation of nickel aluminides, it was reported that [26] when the SO 2 content was increased up to 3%, the oxidation was increased remarkably.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…In the case of the high temperature sulphidation of nickel aluminides, it was reported that [26] when the SO 2 content was increased up to 3%, the oxidation was increased remarkably.…”
Section: Introductionmentioning
confidence: 97%
“…Because of the potential use of nickel aluminides at high temperatures, it is imperative to understand and study their oxidation behavior. It was reported that the types of scale (oxide or mixture of oxides) and scale morphology formed on the surface of the alloy during high-temperature oxidation/or sulphidation were influenced by both the compositions of the gas and the alloy as well as the reaction temperature [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]. Both thermodynamic and kinetic factors should be considered to understand this complex corrosion process.…”
Section: Introductionmentioning
confidence: 99%